Acute changes in neurovascular reactivity after subarachnoid hemorrhage in vivo. Issue 1 (January 2017) - Balbi, Matilde; Koide, Masayo; Schwarzmaier, Susanne M; Wellman, George C; Plesnila, Nikolaus
Subarachnoid hemorrhage causes acute and long-lasting constrictions of pial arterioles. Whether these vessels dilate normally to neuronal activity is of great interest since a mismatch between delivery and consumption of glucose and oxygen may cause additional neuronal damage. Therefore, we investigated neurovascular reactivity of pial and parenchymal arterioles after experimental subarachnoid hemorrhage. C57BL/6 mice were subjected to subarachnoid hemorrhage by filament perforation or sham surgery. Neurovascular reactivity was assessed 3 h later by forepaw stimulation or inhalation of 10% CO2 . Diameters of cerebral arterioles were assessed using two-photon microscopy. Neurovascular coupling and astrocytic endfoot Ca 2+ were measured in brain slices using two-photon and infrared-differential interference contrast microscopy. Vessels of sham-operated mice dilated normally to CO2 and forepaw stimulation. Three hours after subarachnoid hemorrhage, CO2 reactivity was completely lost in both pial and parenchymal arterioles, while neurovascular coupling was not affected. Brain slices studies also showed normal neurovascular coupling and a normal increase in astrocytic endfoot Ca 2+ acutely after subarachnoid hemorrhage. These findings suggest that communication between neurons, astrocytes, and parenchymal arterioles is not affected in the first few hours after subarachnoid hemorrhage, while CO2 reactivity, which is dependent on NO signaling, is completely lost.